Contribution to vibration isolation of wind turbine towers - Καπασακάλης, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Στατικής και Αντισεισμικών Ερευνών, 2017)
The subject of this master thesis is the study of the dynamic behavior of wind turbines under seismic and wind loads. More specifically, the critical factor for the function of wind turbines is fatigue, both for the wind turbine tower and for the foundation. The fatigue is directly related to the stress of the tower, the foundation and the dynamic response of the wind turbine. The purpose of this master thesis is the investigation of the influence that the isolation systems have, in the degradation of the response of the structure, under dymanic loads. The isolation systems that are taken into consideration are the classical Tuned Mass Damper, in various implementations, and a novel passive vibration isolation system the KDamper, which incorporates negative stiffness elements in the classical Tuned Mass Damper isolation system. As an introduction to the subject, a brief review in the types of wind turbines and the influence they have in the modern world is presented in Chapter 1. In the second chapter of the thesis, a bibliographic review on the passive isolation systems of Tuned Mass Damper and KDamper is presented. Subsequently, the outline of these isolation systems is presented and the equations that consider a Single Degree of Freedom system combined with the respective isolation system, are formed, and a comparison between them is made after the optimization of their parameters. In the 3rd Chapter, the modeling of the wind turbine tower is described, in the MATLAB environment, for the case of the uncontrolled wind turbine tower and for every implementation of the respective isolation system that is considered. In Chapter 4, the results of the dynamic parametric analysis of the wind turbine tower are being compared for every dynamic load and isolation system that were tested. The factors that were considered critical for this thesis, are the displacement of the top of the tower, because it is closely related to the manifested forces and the fatigue they result in, and the relative displacement of the top of the tower and the isolation system.